2022
DOI: 10.3390/biom12050702
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the Peritumoral Adipose Tissue Microenvironment as an Innovative Antitumor Therapeutic Strategy

Abstract: The tumor microenvironment (TME) plays a key role in promoting and sustaining cancer growth. Adipose tissue (AT), due to its anatomical distribution, is a prevalent component of TME, and contributes to cancer development and progression. Cancer-associated adipocytes (CAAs), reprogrammed by cancer stem cells (CSCs), drive cancer progression by releasing metabolites and inflammatory adipokines. In this review, we highlight the mechanisms underlying the bidirectional crosstalk among CAAs, CSCs, and stromal cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(40 citation statements)
references
References 160 publications
0
40
0
Order By: Relevance
“…As mentioned, under exposure to cancer cells, adipocytes can transform into cancer-associated adipocytes [ 7 ]. Zoico et al revealed that during interaction with colon cancer cells, adipocytes obtained from 3T3-L1 cells can be reprogrammed into CAAs or dedifferentiated into “fibroblast-like cells” in vitro [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As mentioned, under exposure to cancer cells, adipocytes can transform into cancer-associated adipocytes [ 7 ]. Zoico et al revealed that during interaction with colon cancer cells, adipocytes obtained from 3T3-L1 cells can be reprogrammed into CAAs or dedifferentiated into “fibroblast-like cells” in vitro [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the production and secretion of a wide array of effectors, including exosomes, lipids, and adipokines, AT can have paracrine and endocrine effects that control metabolic homeostasis [ 6 ]. Aside from their physiological functions, these secreted factors may play a crucial role in cancer proliferation, invasion, and resistance to therapies [ 7 ] and may be involved in the initiation and progression of CRC [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations